Geomorphic classification of coral reefs in the north-western Australian shelf - Kordi, Moataz Nael S; O'Leary, Mick (Elsevier BV, 2016)
Coral reefs occur extensively along the northwest Australian continental shelf in the Kimberley Bioregion (KIM), forming major geomorphic features along and just off the coast. These reefs have not been studied in as much detail as the offshore reefs and are poorly known due to the coastal conditions, including extremely high tide regimes, high turbidity and complex coastline morphology. This study aims to establish a regional-scale distribution map of exposed and intertidal reefs of the KIM and to classify the Kimberley reefs into types, adopting widely recognised reef classification and typology schemes. Remote sensing and Geographic Information Systems (GIS) were used in this study to process and produce digital maps as well as to provide some of the first detailed spatial analysis of reef distribution. Outcomes of this study showed that the Kimberley reefs possess strong morphological complexity and clear regional patterns. The study revealed that the number of Kimberley reefs and their area are considerably (60%) greater than previously thought; the total combined reefal area is approximately 1,950 km2. Fringing reefs have been identified as the dominant reef type and are widely distributed throughout the KIM. It was also found that tidal range affected the distribution of reef geomorphologies. The outcomes of this study will contribute to a better understanding of the Kimberley reefs, and provide marine park managers with essential and quality scientific information so that better management decisions can be made in this area.